TiO2 Nanotubes Functionalized with Icariin for an Attenuated In Vitro Immune Response and Improved In Vivo Osseointegration - Andreea-Mariana Negrescu; Valentina Mitran; Wanda Draghicescu; Simona Popescu; Cristian Pirvu; Iuliana Ionascu; Teodoru Soare; Seralp Uzun; Sorin Mihai Croitoru; Anisoara Cimpean (Journal of Functional Biomaterials, 2022)
Due to their superior mechanical and chemical properties, titanium (Ti) and its alloys have been widely used as orthopedic implantable devices. However, their bioinertness represents a limitation, which can be overcome by employing various surface modifications, such as TiO2 nanotube (TNT) fabrication via electrochemical anodization. Anodic TNTs present tunable dimensions and unique structures, turning them into feasible drug delivery platforms. In the present work, TNTs were loaded with icariin (Ica) through an adhesive intermediate layer of polydopamine (DP), and their in vitro and in vivo biological performance was evaluated. The successful fabrication of the modified surfaces was verified by scanning electron microscopy (SEM), atomic force microscopy (AFM), Fourier transform infrared spectroscopy (FTIR), and contact angle measurements (CA), while the in vitro release of Ica was evaluated via UV-VIS spectrophotometry. In terms of in vitro behaviour, comparative studies on RAW 264.7 macrophages demonstrated that the TNT substrates, especially TNT-DP-Ica, elicited a lower inflammatory response compared to the Ti support. Moreover, the in vivo implantation studies evinced generation of a reduced fibrotic capsule around this implant and increased thickness of the newly formed bone tissue at 1 month and 3 months post-implantation, respectively. Overall, our results indicate that the controlled release of Ica from TNT surfaces could result in an improved osseointegration process.